National code in the traditions of the Kazakh people - Kurmangali, F.T.; Mamayeva, G.B.; Kereyeva, N.Zh. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
The article examines the national code embodied in Kazakh traditions and its manifestation in the linguistic worldview through a linguocultural lens. It highlights how cognition, being, customs, and traditions embody the essence of cultural values within the worldview of an ethnos. Kazakh traditions, seen as a national code, preserve historical and cultural heritage and serve as one of the key spiritual values of the people. In this sense, tradition functions as the genetic code of the Kazakh nation. Within linguistics, the anthropocentric paradigm examines the interconnection of language, culture, and human experience, linking language to centuries of collective knowledge, cognition, and cultural memory. The study of linguocultural cognition and the national code is essential for understanding cultural identity, worldview, and the unique character of a nation through its linguistic data. Accordingly, the article’s main aim is to identify customs and traditions that embody the cultural values of the Kazakh people as a national code. In this research, linguistic units connected with Kazakh customs and traditions were analyzed.